Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0972150919848938
|View full text |Cite
|
Sign up to set email alerts
|

Information Sources and the Tourism Decision-making Process: An Examination of Generation X and Generation Y Consumers

Abstract: Generation Y (Gen Y) is becoming more important to marketers as its members continue to enter the workforce. Members of this generational cohort are essential to the tourism industry as they engage in planning vacations themselves. This study accesses the information search behaviour of Gen Y and makes comparisons to the previous generation, Generation X (Gen X). A demographic profile, including information sources, is compiled. Additionally, several proposals were developed based upon the literature regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73]. Moreover, cross-generational differences were studied in retailing regarding products in the non-food sector [74][75][76][77], in technology adoption or purchase [78,79], as well as politics [80].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While multigenerational cohort studies or cross-generational studies have been detected in different areas of academic research, most of the studies focus on generational differences in the workplace [59][60][61]. Yet, other academic fields also encompass cross-generational differences, such as the travel and tourism industry [62][63][64][65]; the health, mental, cognition, or psychology sector examining related issues [66][67][68]; the service sector [69][70][71]; and studies in education [72,73]. Moreover, cross-generational differences were studied in retailing regarding products in the non-food sector [74][75][76][77], in technology adoption or purchase [78,79], as well as politics [80].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, since the backpacker segment is predominantly made up of younger tourists who organize their visits independently, it is expected that new technologies will play a very important role in the preparation of their trips and even during the visits they make to a given destination. Reisenwitz and Fowler (2019) compared the information search process between Generation Y‐ers (born between 1977 and 1994) and Generation X‐ers (born between 1965 and 1976) and conclude that Generation Y tourists, who have a high use of online social interaction, use more technologies to search for information when planning their trips. Focusing in the differences on the use of social media for travel, Amaro et al (2016) also identified different segments among travelers according to the degree of involvement in consumption and creation of travel contents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tourists avoid destinations perceived risky because of higher safety concerns (Cossens & Gin, 1995;Demos, 1992;Pinhey & Iverson, 1994;Sönmez & Graefe, 1998b). Researchers find that tourists with proper information and exposure to destination are less affected by risk perceptions (Lepp et al, 2011;Reisenwitz & Fowler, 2019). Studies find that past travel experiences and sources of information assist in balancing risk perceptions and destination choice (Pizam & Fleischer, 2002;Sönmez & Graefe, 1998a;Um & Crompton, 1990;Witt & Moutinho, 1989).…”
Section: Perceived Risks and Tourist Behaviourmentioning
confidence: 99%